2020
DOI: 10.1111/mec.15722
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of cytosine methylation does not remove latitudinal clines in two invasive goldenrod species in Central Europe

Abstract: Invasive species frequently differentiate phenotypically in novel environments within a few generations, often even with limited genetic variation. For the invasive plants Solidago canadensis and S. gigantea, we tested whether such differentiation might have occurred through heritable epigenetic changes in cytosine methylation. In a 2-year common-garden experiment, we grew plants from seeds collected along a latitudinal gradient in their non-native Central European range to test for trait differentiation and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 160 publications
(203 reference statements)
1
18
0
Order By: Relevance
“…Several studies have shown that variation in cytosine methylation might be associated with differentiation between local habitat conditions or along climatic gradients: for example in the clonal invasive species Reynoutria japonica (Richards et al, 2012) and the poleward range-expanding apomictic plant species Taraxacum officinale (Preite et al, 2015). Since variation in cytosine methylation was suggested as a response to changing environments (Münzbergová et al, 2019), it could also be involved in the formation of altitudinal (Alexander et al, 2009;Moran et al, 2017) and latitudinal clines across the invasive range (Kollmann and Bañuelos, 2004;Eckert et al, 2021), or related to invasion dynamics due to landscape heterogeneity (Deutschewitz et al, 2003;Eschtruth and Battles, 2009). Invasive plant species are exposed to novel environmental conditions often combined with high disturbance levels in their new range (Theoharides and Dukes, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that variation in cytosine methylation might be associated with differentiation between local habitat conditions or along climatic gradients: for example in the clonal invasive species Reynoutria japonica (Richards et al, 2012) and the poleward range-expanding apomictic plant species Taraxacum officinale (Preite et al, 2015). Since variation in cytosine methylation was suggested as a response to changing environments (Münzbergová et al, 2019), it could also be involved in the formation of altitudinal (Alexander et al, 2009;Moran et al, 2017) and latitudinal clines across the invasive range (Kollmann and Bañuelos, 2004;Eckert et al, 2021), or related to invasion dynamics due to landscape heterogeneity (Deutschewitz et al, 2003;Eschtruth and Battles, 2009). Invasive plant species are exposed to novel environmental conditions often combined with high disturbance levels in their new range (Theoharides and Dukes, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we focused on Solidago canadensis s.l., a perennial Asteraceae, which is invasive in Central Europe, as well as in many other parts of the world, and which has formed latitudinal clines that persist even when plants are grown in common-garden environments (Weber and Schmid, 1998;Li et al, 2016;Eckert et al, 2021). Eckert et al (2021) found that in Central Europe these clines persisted in offspring that have been treated with the cytosine demethylation agent zebularine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to using transcriptomics approaches, several authors have argued that epigenetic mechanisms could be particularly important for invasive species (Ardura et al, 2017;Hawes et al, 2018;Marin et al, 2020;Mounger et al, 2021a; but see Eckert et al, 2021). The case has been made particularly for those invasive species that are clonal or have low genetic diversity.…”
Section: Discoveries and Limitations Of Genomic Studies Of Diverse Invasive Speciesmentioning
confidence: 99%